STRATEGIC DISASTER MANAGEMENT WITH ‘FAMILY’ AS A DECISION LAYER AND PARTICIPATORY LOCAL PLANNING (Third Sector Social Economic Review, 2018)
Disaster risks are usually managed by central planning functions of national governments, consequently local knowledge of various geographies and cultures cannot be transferred to the planning processes effectively. This situation leads to the lack of community support for the disaster risk management issues. Article models three strategic decision layers, namely (1) national management, (2) risk mitigation planning group which is formed by related shareholders and stakeholders, and (3) family, to manage disaster risks effectively; and calls it as ‘strategic disaster management’. Model claims that participation in the planning processes of which local knowledge is made use causes public motivation on support of disaster management processes and forms social consciousness as well.
Keywords: disaster management; strategic management; strategic planning; risk governance; participatory planning; interdisciplinary participation; local government